Need for drug delivery systems 1 - Silva, Ana Catarina (Henry Stewart Talks, 2019)
Conventional pharmaceutical dosage forms, Strategies to improve drug bioavailability, Liposomes, Micelles, Nanoemulsions, Microemulsions, Nanoparticles, Polymeric and lipidic nanoparticles, Dendrimers, Limitations of nanosystems